Votes for Women: Electoral Systems and Support for Female Candidates. Issue 1 (12th January 2017) - Golder, Sona N.; Stephenson, Laura B.; Van der Straeten, Karine; Blais, André; Bol, Damien; Harfst, Philipp; Laslier, Jean-François
Abstract : It is a well-established finding that proportional representation (PR) electoral systems are associated with greater legislative representation for women than single member systems. However, the degree to which different types of PR rules affect voting for female candidates has not been fully explored. The existing literature is also hampered by a reliance on cross-national data in which individual vote preferences and electoral system features are endogenous. In this study, we draw upon an experiment conducted during the 2014 European Parliament (EP) elections to isolate the effects of different PR electoral systems. Participants in the experiment were given the opportunity to vote for real EP candidates in three different electoral systems: closed list, open list, and open list with panachage and cumulation. Because voter preferences can be held constant across the three different votes, we can evaluate the extent to which female candidates were more or less advantaged by the electoral system itself. We find that voters, regardless of their gender, support female candidates, and that this support is stronger under open electoral rules.